Computer organization and embedded systems - Hamacher, V. Carl; Vranesic, Zvonko; Zaky, Safwat; Manjikian, Naraig (McGraw Hill, 2012)
Covers the key topics in computer organization and embedded systems. This title presents hardware design principles and shows how hardware design is influenced by the requirements of software. It explains the main principles supported by examples drawn from commercially available processors.